The dream is over : the crisis of Clark Kerr's California idea of higher education - Marginson, Simon, 1951- (Clark Kerr lectures on the role of higher education in society, 2016)
"The Dream Is Over tells the extraordinary story of the 1960 Master Plan for Higher Education in California, created by visionary University of California President Clark Kerr and his contemporaries. The Master Plan's equality of opportunity policy brought college within reach of millions of American families for the first time and fashioned the world's leading system of public research universities. The California idea became the leading model for higher education across the world and has had great influence in the rapid growth of universities in China and East Asia. Yet remarkably, the political conditions supporting the California idea in California itself have evaporated. Universal access is faltering, public tuition is rising, the great research universities are under growing pressure, and educational participation in California, once the national leader, lags way behind. Can the social values embodied in Kerr's vision be renewed?"--Provided by publisher